Utilizing Artificial Intelligence (AI) in Customer’s Purchase Intentions on Online Food Delivery Service - Thevisri Ravi; Rosmelisa Yusof; Loke Kean Koay; Yee Teng Teoh; Mun Yee Thin; Tiffany Audrey Anak Donold; Nur Aini Raudhatul Jannah; Prachi Mittal; Rishabh Srivastava; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
Generally, food delivery services like GrabFood act as couriers, transporting consumer needs from restaurants or stores directly to their doorsteps. The rise of Artificial Intelligence (AI) has further revolutionized this convenience, allowing people to order meals and other goods from the comfort of their homes. This research investigates how AI is utilized to influence customer purchase intentions on GrabFood. The study examines the impact of six independent variables: instant food delivery, estimated delivery time, customized food recommendations, interactivity, cashless payment methods, and consumer behavior. These variables are analyzed in relation to the dependent variable – the customer's intention to use GrabFood. To gather data, an online survey was conducted with 100 respondents. The collected data was then verified using SPSS software. The findings revealed that delivery speed is a key driver, with both instant delivery and estimated delivery time showing a significant positive correlation (? = 0.457) with purchase intention. However, other features like personalized recommendations (? = 0.174), cashless payment methods (? = 0.119), and user interaction (? = -0.188) did not significantly impact user decisions. These findings require further exploration to understand user preferences for these features.